Registered Report: How does art impact pain and stress? Exposure to multimodal art (Music + Visual) and music alone enhances pain tolerance more than visual art, but neither art form impacts autonomic or endocrine markers - Anna Fekete; Rosa M. Maidhof; Eva Specker; Andreas Gartus; Urs M. Nater; Helmut Leder (PLoS ONE, 2026)
While the pain- and stress-reducing effects of music are well investigated, effects of visual art and the combination of both modalities (music and visual art) are much less explored. We tested the (1) pain- and (2) stress-reducing effects of a multimodal (music + visual art) aesthetic experience—expecting stronger effects than single modal aesthetic experiences (music or visual art)—and, in an exploratory manner, (3) investigated underlying mechanisms of aesthetic experience and (4) individual differences. In a repeated-measures design (music, visual art, multimodal aesthetic experience, control), 42 female participants submitted their self-selected movingly beautiful visual artworks and music pieces to the lab, where pain and stress were induced by a cold pressor test. Pain (global pain perception, pain intensity, pain affect, pain tolerance) and stress responses (subjective reports, autonomic [electrocardiography, electrodermal activity, salivary alpha-amylase] and endocrine activity [salivary cortisol]) were measured. Individual differences of the experience, trait empathy and absorption were investigated. Exposure to multimodal art resulted in longer pain tolerance ( M = 80.19s; SD = 61.05) compared to visual art ( M = 56.63s; SD = 47.86), but not compared to music ( M = 81.34s; SD = 64.19; p < .001; η ² = .039). Other measures of pain intensity, stress intensity, and pain affect did not differ across the conditions. Exposure to all types of art distracted participants’ attention from pain, prompted mind wandering, and elicited greater enjoyment than the control condition. While participants were overall more stressed during the cold pressor test, no differences emerged across the four conditions ( p = 0.38; η ² = .012). Also, no differences were found regarding cortisol and alpha-amylase. Regarding individual differences, higher trait absorption was associated with longer pain tolerance in the multimodal condition (b = 0.58, SE = 0.29, t (120)=2.02, p = .046) and with lower pain intensity in the music-only condition ( b = −0.27, SE = 0.12, t (120)=−2.20, p = .030), compared to the other conditions. In conclusion, exposure to art can influence pain; however, the underlying mechanisms require further research.